The experiences of pre-service teachers teaching practicum during the COVID-19 pandemic: A systematic literature review - Prescylla Kristyn Kiok (Global Academic Excellence, 2021)
The COVID-19 pandemic has resulted in the prohibition of close contact and this unprecedented issue has led to the abrupt closure of schools and universities across the country. Teacher education programs have taken a toll as the final year students would not be able to fully experience the working environment in a school during teaching practicum. Thus, this systematic literature review aims to explore the lived experiences of pre-service teachers teaching practicum experiences during the COVID-19 pandemic. Hence, after screening from 23,084 research articles, 8 relevant articles that focus on the teaching practicum experiences of pre-service teachers during the pandemic were chosen for review in order to achieve the objective. The findings show that the pre-service teachers teaching practicum experiences can be categorised into intrapersonal development or interpersonal development. Pre-service teachers seem to have a positive perception towards the change as they understood the importance of the transition from face-to-face learning to online learning during the pandemic. Other than that, positive or negative teaching practicum experiences highly depend on the institutions as much as the pre-service teachers depend on themselves. The future agenda and implementation of the findings are also discussed.